Peer relationships as an area of activity for a school class teacher - Muszyńska, Ewa (EDUsfera. Ewa Jurczyk-Romanowska, 2020)
Peer relationships play a significant role in the development of children and adolescents, as evidenced by the negative effects of their irregularities. The school class is an important setting for shaping these relationships
Keywords: peer relationships; interactions; informal group; rejected child; isolated child